When Fathers Feel Socially Constrained to Assume a Role: A Negative Predictor of the Coparental Relationship in Switzerland - Favez, Nicolas; Max, Aline; Bader, Michel; Tissot, Hervé (Frontiers in Psychology, 2022)
Role distribution is a central issue for parents in the transition to parenthood, but little is known about the motivations in fathers to assume a specific role. Differences in work-family balance in each parent may be motivated by an individual choice mutually shared by both partners; however, in many couples, the parents may feel forced to adopt a traditional role distribution, either for financial reasons, or to comply with social expectations about what men and women should do when they are parents. This feeling of being socially constrained to adopt a role distribution that is not congruent with intrinsic motivations can generate dissatisfaction and may jeopardize the development of the interparental relationship. Coparenting refers to the emotional and instrumental support parents bring to each other in their parental tasks. It has been shown to be central in family functioning and a powerful predictor of children’s emotional and cognitive development. In this study, we aimed to assess the extent to which different motivations for role distribution in fathers are predictive of the quality of the coparental relationship. A convenience sample of 144 fathers from the French-speaking part of Switzerland completed online questionnaires about their motivations, coparental relationship, and sociodemographic characteristics. Results showed that the reasons for role distribution were mainly economical, practical, and in order to meet personal expectations. Multivariate general linear modeling showed that role distribution that is constrained to meet social expectations and age were predictive of a less cohesive coparental relationship, whereas a deliberate choice in role distribution was linked to a more cohesive coparental relationship.